Open educational resources third party creators [electronic resource] (RMIT University Library, 2019)
Open Educational Resources (OERs) are any type of educational materials that are in the public domain. They are published under open licenses (i.e Creative Commons) that specify how materials can be used, reused, adapted, shared and modified according to specific needs. They can include textbooks, lecture notes, syllabi, assignments and tests. Open Education resources produced by non-RMIT creators.